2018
DOI: 10.3390/electronics7120428
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Implementation for an Improved Full-Pixel Search Algorithm Based on Normalized Cross Correlation Method

Abstract: Digital speckle correlation method is widely used in the areas of three-dimensional deformation and morphology measurement. It has the advantages of non-contact, high precision, and strong stability. However, it is very complex to be carried out with low speed software implementation. Here, an improved full pixel search algorithm based on the normalized cross correlation (NCC) method considering hardware implementation is proposed. According to the field programmable gate array (FPGA) simulation results, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Zhang et al reported on "Hardware Implementation for an Improved Full-Pixel Search Algorithm Based on Normalized Cross Correlation Method" [4] to propose an improved full pixel search algorithm based on the normalized cross correlation (NCC) method considering hardware implementation. According to the field programmable gate array (FPGA) simulation results, the speed of hardware design proposed in this paper is 2000 times faster than that of software in single-point matching, and 600 times faster than software in multi-point matching.…”
Section: The Topic Of Electronics and Its Applicationsmentioning
confidence: 99%
“…Zhang et al reported on "Hardware Implementation for an Improved Full-Pixel Search Algorithm Based on Normalized Cross Correlation Method" [4] to propose an improved full pixel search algorithm based on the normalized cross correlation (NCC) method considering hardware implementation. According to the field programmable gate array (FPGA) simulation results, the speed of hardware design proposed in this paper is 2000 times faster than that of software in single-point matching, and 600 times faster than software in multi-point matching.…”
Section: The Topic Of Electronics and Its Applicationsmentioning
confidence: 99%
“…The region-based approach directly uses the pixel values for the match. The similarity parameters are measured in detail by aiding the simple image subtraction, such as Sum of Squared Differences (SSD) [12], Sum of Absolute Differences (SAD) [13], and Normalized Cross Correlation (NCC) [14,15]. Unfortunately, these methods are sensitive to transition and rotation changes.…”
Section: Introductionmentioning
confidence: 99%